Use of ultrasonic pachymetry for measurement of changes in corneal thickness in mouse corneal transplant rejection. Issue 3 (12th October 2009) - Flynn, T H; Ohbayashi, M; Dawson, M; Siddique, M; Ono, S J; Larkin, D F P
Abstract : Background/aims: Diagnosis of rejection in the mouse model of corneal transplantation is based on subjective judgement of loss of graft transparency. The aims of this study were to (1) evaluate a pachymetry technique to measure changes in mouse corneal thickness and (2) correlate increases in transplant thickness with clinical and histological features of rejection. Methods: Orthotopic corneal allografts (C57BL/6 strain donor) and syngeneic grafts were performed in A/J mice. Graft transparency was graded and corneal thickness measured by pachymetry on alternate days. Transverse sections of donor cornea excised from eyes representative of clinical opacity grades 1–4 were prepared, photographed, graft section thickness measured and stromal graft-infiltrating cells counted. Intraobserver and interobserver variations in pachymetry were statistically tested. Results: Graft thickness, as measured by pachymetry, increased with each clinical opacity grade. Thickness for opacity grades 0, 1 and 2 was less than 300 μm in all recipients. Graft thickness for grades 3 and 4 was greater than 300 μm in all cases. For measurements up to 400 μm, there was a good correlation between thickness as measured by in vivo pachymetry and in histopathological sections. The mean interobserver bias was −11.35 μm, while the mean intraobserver bias was +3.96 μm. Stromal cellularity increased with increasing corneal thickness up to approximately 300 μm. Conclusion: In vivo graft pachymetry provides a new and reliable way to objectively diagnose rejection in the mouse model of corneal transplantation.